2002
DOI: 10.1063/1.1496661
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear optical spectroscopy of epitaxial magnetic garnet films

Abstract: Second and third harmonic optical spectra are studied in epitaxial magnetic thin films in the spectral ranges 1.7-3.2 eV and 2.4-4.2 eV, respectively. No significant increase of the intensity of the nonlinear spectra is found above the bandgap near 3.2 eV, where the linear absorption increases by two orders of magnitude. Large magnetic contributions to the second harmonic spectra and magnetic contrast as high as 100% are observed at selected photon energies. Contrary to that, no magnetic contribution to the th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Though the review did not cover other types of SHG interactions in detail, electric‐dipole SHG involving spin interactions, as well as magnetic dipole SHG interactions have been widely used to probe magnetic materials. SHG spectroscopy performed with varying incident wavelengths allows for the determination of electronic resonances and magnetic resonances, as well as distinguish ferroelectric and magnetic phase transitions and domain structures in multiferroic materials …”
Section: Conclusion and Future Outlookmentioning
confidence: 99%
See 1 more Smart Citation
“…Though the review did not cover other types of SHG interactions in detail, electric‐dipole SHG involving spin interactions, as well as magnetic dipole SHG interactions have been widely used to probe magnetic materials. SHG spectroscopy performed with varying incident wavelengths allows for the determination of electronic resonances and magnetic resonances, as well as distinguish ferroelectric and magnetic phase transitions and domain structures in multiferroic materials …”
Section: Conclusion and Future Outlookmentioning
confidence: 99%
“…The SHG processes that involve the magnetic field of light are typically weaker; however, they can be sensitive to time reversal symmetry, and hence to the magnetic structure of materials. Thus, SHG has been used extensively to study magnetic and multiferroic materials as well . A chiral structure intrinsically breaks inversion symmetry.…”
Section: Introductionmentioning
confidence: 99%
“…Some features in the SH spectrum can be assigned to the crystal-field Fig. 6 Optical absorption spectra in the three garnet films transitions in the two iron sublattices [21] . Two other sharp absorption features near 2.57 eV (presumably due to the 6A14E 4A1 transition in the tetrahedral sublattice) and 2.66 eV (presumably due to the 6A 1g4Eg,4A1g transition in the octahedral sublattice) are also observed in the SHG spectrum (see Fig.…”
Section: Shg Spectra In Magnetic Garnet Filmsmentioning
confidence: 99%
“…Very recently, Pavlov et al investigated MTHG in a substituted YIG and reported that transmitted TH intensity was unchanged by the transversal external magnetic field. 15 Independently, we studied the MTHG with a bismuth-aluminum-doped YIG ͑Bi,Al:YIG͒ polycrystalline thin film. 16 In this letter, we report that the polarization plane of the TH wave is rotated by applying a longitudinal external magnetic field.…”
mentioning
confidence: 99%